Cholangiocarcinoma: Has There been Any Progress?. (2010) - Meza-Junco, Judith; Montano-Loza, Aldo J; Ma, Mang; Wong, Winnie; Sawyer, Michael B; Bain, Vincent G
Abstract : Cholangiocarcinoma is the second most common primary hepatic tumour after hepatocellular carcinoma. Primary sclerosing cholangitis is one of the most commonly recognized risk factors for cholangiocarcinoma; however, approximately 90% of patients have no identifiable risk factors. Extrahepatic type is its most common presentation. Cholangiocarcinoma is considered to be a devastating disease, with a poor survival rate and few therapeutic options. Although surgical resection has been considered the best treatment option for localized cholangiocarcinoma, local recurrences of this cancer are very common, and imply persistent micrometastatic disease in lymph nodes or at surgical margins, even after extended surgical resection. Consequently, the five-year survival rate after attempted curative resection is only 20% to 40%. Early studies of liver transplantation for cholangiocarcinoma did not show a survival benefit and, currently, this tumour is considered to be an absolute contraindication for liver transplantation in most transplant centres worldwide. Recently, neoadjuvant chemoradiation in combination with liver transplantation for highly selected patients with cholangiocarcinoma has shown impressive results, with five-year survival rates at approximately 76% to 82% – similar to other standard indications for liver transplantation, such as hepatocellular carcinoma or hepatitis C-induced cirrhosis. However, this success of liver transplantation applies to only a subset of patients and most of the data originated from a single centre. Wider application of this strategy, especially for patients with potentially resectable disease, will require validation by other centres.